The experience and insight of survivors who have engaged in a restorative justice meeting with their assailant - Wager Nadia (Temida)
This review study explores the experiences of survivors of sexual violence who engaged in a restorative justice (RJ) meeting with their assailant to ascertain whether the process contributes to, or further compounds, their recovery. This paper forms a small part of a more extensive scoping review employing Arksey and O’Malley’s (2002) framework. The search was confined to articles/reports published in English. Initially, 58 sources were identified as suitable for inclusion and each of these sources were then scrutinised to identify accounts of survivors of sexual violence who have taken part in RJ initiatives that have involved a face-to-face meeting with the assailant. This revealed 10 applicable cases, from across four different countries. The findings suggest that under certain circumstances survivors of sexual violence might receive significant benefit from participating in RJ. The specific conditions under which the benefits appear to be forthcoming and areas for future research are discussed.